Botsman and Clulow, Commemorating Meiji: History, Politics and the Politics of History (Routledge, 2022) - Alison J Miller (Royal Studies Journal, 2022)
Review of Botsman and Clulow, Commemorating Meiji: History, Politics and the Politics of History (Routledge, 2022)